Partial computation offloading method based on joint resource allocation for mobile edge computing - Yao LIU; Yueyuan HE; Hongjing ZHOU; Chaoliang LI; Chuang LI (物联网学报)
In order to meet the requirements of users for computing-intensive tasks and solve the problems of limited computing resources and energy of mobile terminals, a partial offloading method was proposed for multi-user mobile edge computing system with orthogonal frequency division multiple access by setting constraints such as task delay, device energy and communication resources, aiming at optimizing task delay.The initial offloading ratio was set and the communication resource was allocated under the condition of satisfying the user’s minimum delay.And then the remaining computing resource was allocated according to the server’s computing capability.Finally, the offload ratio was optimized according to the resource allocation.Simulation results show that this method can reduce the delay of task computing and the energy consumption of mobile terminals.